Blasphemy and religious defamation: what are the limits to our freedom? - Wan Mohd Nor, Murni (IKIM Press, 2019)
Incidences of blasphemy and religious defamation occur around the world, often provoking angry, and sometimes violent reactions from religious adherents. However, laws prohibiting blasphemy and religious defamation are heavily criticised as being against freedom of speech, despite their effect on race relations. This article highlights the position of blasphemy and religious defamation according to International Law, and presents counterarguments of the main objections to such laws. It also highlights the issue from the Islamic perspective, and offers an alternative approach to interpreting human rights. This article concludes by explaining the need for human rights and free speech to be interpreted according to common moral and religious values, and emphasising the purpose of human rights and free speech—which should be for the attainment of justice. In doing so, it is hoped that there will be a better balance in enforcing the right to free speech, as well as the protection of religious sensitivities.